2021
DOI: 10.1007/s00128-021-03184-w
|View full text |Cite|
|
Sign up to set email alerts
|

Biomonitoring of Toxic Metals in Feathers of Birds from North-Eastern Pakistan

Abstract: The current study was designed to determine the concentrations of toxic metals (Ni, Pb and Cr) in feathers of birds collected from four regions of NE Pakistan. Feather samples of birds (House Crow, Common Myna and House Sparrow) were collected from different areas. Atomic absorption spectrophotometer was used to determine the concentration of metals in feathers. Analysis of the data revealed that concentrations of Pb and Cr were significantly different (p < 0.05) among bird species, whereas no difference (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
(49 reference statements)
2
4
1
Order By: Relevance
“…It prefers to inhabit more crowded urbanized areas with high traffic, which make it exposed to Pb emission more than swallows and doves that prefer more rural areas than urbanized ones. This finding was consistent with the study done in Pakistan, they found a high concentration of Pb in house sparrows (Aziz et al, 2021), especially those near heavy traffic. The consequences of pollution that could be Pb or other sources of pollutants are indicated in a clear way in the testes of house sparrow males that suffered from regressed testicular tissues more than laughing doves and swallows.…”
Section: Discussionsupporting
confidence: 93%
“…It prefers to inhabit more crowded urbanized areas with high traffic, which make it exposed to Pb emission more than swallows and doves that prefer more rural areas than urbanized ones. This finding was consistent with the study done in Pakistan, they found a high concentration of Pb in house sparrows (Aziz et al, 2021), especially those near heavy traffic. The consequences of pollution that could be Pb or other sources of pollutants are indicated in a clear way in the testes of house sparrow males that suffered from regressed testicular tissues more than laughing doves and swallows.…”
Section: Discussionsupporting
confidence: 93%
“…Chromium is a non-essential element and accumulations of it cause complications in the reproductive systems of birds (Aziz, et al, 2021). The unceasing amounts of chromium in avian species has been recorded worldwide in the areas where leather industry is dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The level of heavy metals in Pb and Cd was significantly correlated with both raw-unclean and raw-clean EBNs (Table -3). The correlation between Pb and Cd indicated that a link existed between these metals during the contamination [44] of EBNs in SFHs.…”
Section: Correlation Between Heavy Metals In Raw-unclean and Raw-clea...mentioning
confidence: 95%